2008
DOI: 10.1007/s00421-008-0863-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiological demands of different sailing techniques of the new Olympic windsurfing class

Abstract: The introduction of the new Olympic class windsurf-board has prompted sailors to develop a new technique of sail "pumping" (rhythmically pulling the sail so that it acts as a wing). Contrary to the old technique that mainly involved upper body activity, the new one requires both upper and lower body muscle activity. Accordingly, the aim of the present study was to compare the performance characteristics of the board (speed and pointing angle ability relative to the direction of the wind) as well as the sailors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 9 publications
1
37
0
Order By: Relevance
“…Comparable or greater values for metabolic response have been observed in boardsailing by De Vito et al (1996& 1997, and more recently, Castagna et al (2007;2008) reported oxygen uptake values of 65 ml*kg -1 *min -1 , or above 80% of VO 2 max, with heart rates above 90% of HRmax and serum lactate exceeding 10 mmol*l -1 in elite Olympic board sailors when recorded during highly taxing conditions on water (characterized by light wind and down-wind sailing where immense sail pumping (i.e. manual repetitive movements with the rig) contributes as a main factor to propulsion).…”
Section: On-water Assessmentsmentioning
confidence: 56%
“…Comparable or greater values for metabolic response have been observed in boardsailing by De Vito et al (1996& 1997, and more recently, Castagna et al (2007;2008) reported oxygen uptake values of 65 ml*kg -1 *min -1 , or above 80% of VO 2 max, with heart rates above 90% of HRmax and serum lactate exceeding 10 mmol*l -1 in elite Olympic board sailors when recorded during highly taxing conditions on water (characterized by light wind and down-wind sailing where immense sail pumping (i.e. manual repetitive movements with the rig) contributes as a main factor to propulsion).…”
Section: On-water Assessmentsmentioning
confidence: 56%
“…The age of these sailors was higher than those of the Optimist and Windsurfing classes, thus the greater value in the levels of strength could be related to a greater development of skeletal muscle structures ( Table 2). Despite this age difference, it would be expected of the sailors of the Windsurfing class to present greater strength values in the hand grip test due to the improvements acquired by the specific practice of their sport [4][5][6]. In flexibility, only the sailors of the Windsurfing class had better results than those of the Laser class ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Windsurfing class boats, the strength of the upper limbs is directly related to the sailor's performance [4]. With the action of the flexors of the fingers, together with the that of the flexors of the elbows, the sailor controls the boat sail, which controls the direction and speed of the vessel [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Its practice depends on three basic conditions: the athlete, environment, and equipment. Little is known about metabolism in windsurfing athletes because most articles in this area have focused on physiological parameters (Campillo et al, 2007;Castagna et al, 2007Castagna et al, , 2008Chamari et al, 2003;Melis et al, 2003;Pérez-Turpin et al, 2009;Vogiatzis et al, 2002) and injuries (Dyson et al, 2006;Hetsroni et al, 2006;McCormick and Davis, 1988;Nathanson and Reinert, 1999;Nathanson et al, 2008;Neville and Folland, 2009;Nickel et al, 2004;Orchard et al 2002;Petersen et al, 2003).…”
Section: Introductionmentioning
confidence: 97%